Banding profiles of green-lipped mussel. Perna viridis (MOLLUSCA, MYTILIDAE) from Mabatan, Sibacan and Wawa, Bataan, Philippines using microsatellite markers. - Golingay, Justine Mary A. (2017.)
Green mussles, Pernaviridis, is widely distributed along the coastal area of the Philippines and is used economically as a cheap source of food. Even so, there is still a lack of quality control and safety of these wild species in the Philippines. Culturing these mussels is just one of the solutions to address this dilemma to insure the quality of the green mussel to be at its best. This study aims to determine the banding patterns of Pernaviridis from Mabatang, Sibacan, and Wawam Bataan, Philippines using microsatellite markers PCAN 10-44 and VJ 1-23-2. Specifically, it aims to determine the length of alleles per site per microsatellite marker. Polymerase Chain Reaction (PCR) was used to analyze the samples from 3 sites in Bataan. The results showed that for PCAN 10-44, all sites have at least 4-6 alleles. However, for VJ 1-23-2 there were several variations. Wawa has 2 alleles, Mabatang has 2-5 alleles and Sibacan has 2-6 alleles. The size range for Mabatang, Sibacan and Wawa, Bataan is <100-1000bp, <100-800bp and <100-623.3 b, respectively for PCAN 10-44. In the case of VJ 1-23-2, the size range for each site is 200-900bp, <50-1000bp and 55.5-215.4bp, respectively. The predominant banding pattern observed for both markers is the presence of two close bands below the 100bp baseline ladder. Differences in the banding patterns would indicate genetic variation thus increasing the chances of survival of mussel populations. The results will contribute to the formulation of effective measures in managing mussel production and the production of good quality broodstockto used for farmers.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Perna viridis; Banding patterns; Microsattelite markers; Polymerase chain reaction (PCR); Bataan, Philippines